Dosimetry for the study of medical radiation workers with a focus on the mean absorbed dose to the lung, brain and other organs. (3rd April 2022) - Yoder, Robert C.; Dauer, Lawrence T.; Balter, Stephen; Boice, John D.; Grogan, Helen A.; Mumma, Michael T.; Passmore, Christopher N.; Rothenberg, Lawrence N.; Vetter, Richard J.
Abstract: Background: The reconstruction of lifetime radiation doses for medical workers presents special challenges not commonly encountered for the other worker cohorts comprising the Million Worker Study. Methods: The selection of approximately 175, 000 medical radiation workers relies on using estimates of lifetime and annual personal monitoring results collected since 1977. Approaches have been created to adjust the monitoring results so that mean organ absorbed doses can be estimated. Results: Changes in medical technology and practices have altered the radiation exposure environments to which a worker may have been exposed during their career. Other temporal factors include shifts in regulatory requirements that influenced the conduct of radiation monitoring and the changes in the measured dose quantities. Conclusions: The use of leaded aprons during exposure to lower energy X rays encountered in fluoroscopically based radiology adds complexity to account for the shielding of the organs located in the torso when dosimeters were worn over leaded aprons. Estimating doses to unshielded tissues such as the brain and lens of the eye become less challenging when dosimeters are worn at the collar above the apron. The absence of leaded aprons in the higher energy photon settings lead to a more straightforward process of relating dosimeter results to mean organ doses.